A Self-Regulation Program on Dietary Consumption, Exercise, and Weight Gain for Overweight and Obese Pregnant Women - Pinitlertsakun, Orrawan; Limruangrong, Piyanun; Sinsuksai, Nittaya; Boriboonhirunsarn, Dittakarn (Nursing Science Journal of Thailand, 2019)
Purpose: To determine the effects of a self-regulation program on dietary consumption, exercise, and weight gain in overweight and obese pregnant women. Design: Quasi-experimental research. Methods: The participants were 70 overweight and obese pregnant women who visited the antenatal care unit, at a university hospital. The participants were divided into the control and experimental groups with 35 each. The control group received routine care and were taught knowledge about overweight and obesity in pregnancy and weight gain control. The experimental group were trained in self-regulation skill that included self-observation, judgment process, and self-reaction. Data were collected using the personal data form, the diet and exercise record sheets, and the weight gain record form at the fourth, and the eighth weeks after the initiation of the intervention. Data analysis was performed with chi-square, Fisher’s exact test and relative risk. Main findings: The experimental group had less likelihood of having uncontrolled dietary consumption at fourth week and eighth week after the program (RR .36, 95%CI .20,.66 vs RR .19, 95%CI .07,.50, respectively), uncontrolled exercise (RR .25, 95%CI .11,.59 vs RR .20, 95%CI .09,.46, respectively), and uncontrolled weight gain (RR .63, 95%CI .40,.97 vs RR .61, 95%CI .38,.97, respectively), compared to the control group. Conclusion and recommendations: The self-regulation program could alter diet and exercise behaviors progressively and controlled weight gain better than the routine care. Midwives should apply the self-regulation program to encourage the overweight and obese pregnant women control their diet, exercise and weight gain.